Absolute Quantification of Phosphor‐Containing Metabolites in the Liver Using 31P MRSI and Hepatic Lipid Volume Correction at 7T Suggests No Dependence on Body Mass Index or Age. Issue 2 (6th October 2018) - Pfleger, Lorenz; Gajdošík, Martin; Wolf, Peter; Smajis, Sabina; Fellinger, Paul; Kuehne, Andre; Krumpolec, Patrik; Trattnig, Siegfried; Winhofer, Yvonne; Krebs, Michael; Krššák, Martin; Chmelík, Marek
Abstract : Background: Hepatic disorders are often associated with changes in the concentration of phosphorus‐31 ( 31 P) metabolites. Absolute quantification offers a way to assess those metabolites directly but introduces obstacles, especially at higher field strengths (B0 ≥ 7T). Purpose: To introduce a feasible method for in vivo absolute quantification of hepatic 31 P metabolites and assess its clinical value by probing differences related to volunteers' age and body mass index (BMI). Study Type: Prospective cohort. Subjects/Phantoms: Four healthy volunteers included in the reproducibility study and 19 healthy subjects arranged into three subgroups according to BMI and age. Phantoms containing 31 P solution for correction and validation. Field Strength/Sequence: Phase‐encoded 3D pulse‐acquire chemical shift imaging for 31 P and single‐volume 1 H spectroscopy to assess the hepatocellular lipid content at 7T. Assessment: A phantom replacement method was used. Spectra located in the liver with sufficient signal‐to‐noise ratio and no contamination from muscle tissue, were used to calculate following metabolite concentrations: adenosine triphosphates (γ‐ and α‐ATP); glycerophosphocholine (GPC); glycerophosphoethanolamine (GPE); inorganic phosphate (Pi ); phosphocholine (PC); phosphoethanolamine (PE); uridine diphosphate‐glucose (UDPG); nicotinamide adenine dinucleotide‐phosphate (NADH); and phosphatidylcholine (PtdC). Correction for hepatic lipid volume fraction (HLVF) was performed. Statistical Tests: Differences assessed by analysis of variance with Bonferroni correction for multiple comparison and with a Student's t ‐test when appropriate. Results: The concentrations for the young lean group corrected for HLVF were 2.56 ± 0.10 mM for γ‐ATP (mean ± standard deviation), α‐ATP: 2.42 ± 0.15 mM, GPC: 3.31 ± 0.27 mM, GPE: 3.38 ± 0.87 mM, Pi : 1.42 ± 0.20 mM, PC: 1.47 ± 0.24 mM, PE: 1.61 ± 0.20 mM, UDPG: 0.74 ± 0.17 mM, NADH: 1.21 ± 0.38 mM, and PtdC: 0.43 ± 0.10 mM. Differences found in ATP levels between lean and overweight volunteers vanished after HLVF correction. Data Conclusion: Exploiting the excellent spectral resolution at 7T and using the phantom replacement method, we were able to quantify up to 10 31 P‐containing hepatic metabolites. The combination of 31 P magnetic resonance spectroscopy imaging data acquisition and HLVF correction was not able to show a possible dependence of 31 P metabolite concentrations on BMI or age, in the small healthy population used in this study. Level of Evidence : 2 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2019;49:597–607.